Peer Editing on Learner’s Writing Skill in a Second-Grade Classroom - Nailul Fauziyah (Journal of Research in Foreign Language Teaching (JRFLT), 2018)
This research attempted at knowing the implementation of peer-editing technique in learners’ English writing skill and their perceptions to peer-editing for teaching and learning writing. The method used in this research is qualitative study. The subjects of this research were 22 learners of the second semester of English Department of University of Pesantren Tinggi Darul Ulum (Unipdu) Jombang of 2015/2016 academic year. The instrument for collecting data was students’ descriptive texts and questionnaire. The data were analyzed by descriptive analysis. The results of the research showed that, in general, peer-editing technique made the learners’ progress on their writing achievement and good perceptions for teaching and learning writing skill of English. This implied that the implementation of peer-editing is significantly improving learners’ writing skill